(untitled) - Cozby, Paul C. (Boston, 2006)
With its concise and strategic approach to decision making, Methods in Behavioral Research by Paul C. Cozby continues to gain in popularity among instructors and students alike. Building on a strong foundation of pedagogy and well-chosen examples, the ninth edition incorporates learning objectives, new graphics and activities to increase student involvement, and an updated appendix on writing research reports as well as making poster presentations
Keywords: Psychology,Social sciences,Phương pháp nghiên cứu tâm lý,Phương pháp nghiên cứu xã hội; Research,Methodology,Research,Methodology